HIJRAH AMONG THE YOUTH: RELIGIOUS CONVERSION AND MODES OF UNDERSTANDING OF RELATED QUR`ĀNIC VERSES - Wardani, Wardani; Mahfuzh, Taufik Warman; Bashori (UIN Antasari Banjarmasin, 2024)
This article aims to analyze the phenomenon of hijrah, e.g. spiritual change in self into being religious or more religious, among the youth which are university students at Universitas Lambung Mangkurat (ULM), Banjarmasin, South Kalimantan, Indonesia, focusing on three main issues. First, religious conversion which is caused by factors. Second, their justification for it by ways of understanding related Quranic verses concerning four issues: the hijrah as a prerequisite of the true belief in Islam, the relation between the hijrah and jihād (warfare), the lawfulness or unlawfulness of an unbeliever’s leadership, and the merits of the hijrah and jihād. Third, psychological, sociological, economic, and religious backgrounds behind this phenomenon and its justification through understanding some Qur`anic texts. Employing a mix of quantitative and qualitative methods and applying Heirich’s religious conversion theory of this phenomenon and Wolfgang Iser’s reception theory of the exegesis of the sacred texts, it concluded as follows. First, the hijrah has been done for reasons, namely theologically believed in God’s guidance, education, and psychological factors. Second, about 60-70% of them agree with the common understanding of Muslim interpreters concerning the interpretation of verses on these four issues. Third, in responding to three main Quranic verses frequently used on the internet for the propagation of the hijrah, their understanding of verses tends to use rational technics of interpretation (ra’y), such as analogical reasoning rather than revelatory ones (sacred text, riwāyah). They also apply theological, legal, and spiritual “paradigms of interpretation”, and even sometimes interpret verses applying a holistic view of Islamic teachings.